Assessment of in-service stresses in steel bridges for high-frequency mechanical impact applications. (15th August 2021) - Shams-Hakimi, Poja; Carlsson, Fredrik; Al-Emrani, Mohammad; Al-Karawi, Hassan
Highlights: The traffic in-service stresses are larger than the one suggested by load model 3. Overload and variable amplitude loading effects on HFMI treated details are studied. The simulation reveals high and varying mean stresses and stress ratios in bridges. Fatigue-critical locations in bridges are the same before and after HFMI treatment. Compressive overloads are not dangerous for fatigue behavior of HFMI treated welds. Abstract: The application of high-frequency mechanical impact (HFMI) treatment to improve the fatigue performance of composite steel and concrete road bridges was studied through a state-of-the-art review in conjunction with simulations of variable amplitude in-service stresses in four case-study bridges in Sweden. Empirical stress range spectra with associated mean stresses were characterised for HFMI-treated bridges. It was shown that the fatigue-critical locations in HFMI-treated bridges remain unchanged compared with conventional bridges and that compressive overloads pose no detrimental effect that requires additional attention in the fatigue assessment. Calculations also showed a considerably better fatigue performance if HFMI treatment is performed on site, after the application of self-weight stresses.